Design and fabrication of smart mousetrap - Vorathin, E. (2011)
The objective of this thesis is to design and fabricate a smart mousetrap to improve product in the market to catch more than one mouse and the mousetrap is safe for human and pets at home. This mousetrap is easy to use and not complicated. It also can be use oftenly, which mean that it can be use over and over again. The mousetrap also has no any poisonous or harmful substance use and the most important is that the mousetrap is safe to human where it will not injure the user. It also can catch up to maximum of four mouse. The material used in fabricating this mousetrap is galvanized iron sheet because the galvanized iron is cheap and easy to fabricate. Other materials that are used in fabricating this mousetrap are Perspex, fastener such as screws and rivet, handle, lock and door slot. The process have been involved in the project are cutting, bending, drilling and riveting. Solidwork Simulation Xpress software is used to simulate the stress analysis on critical part of the mousetrap. From the observation, handle support will be a critical part to sustain a maximum load. Lastly, the objective of this project has been achieved where the mousetrap can catch up to more than one mouse and it is safe to be use where it does not bring harm or any injury to the user and also pets at home